Effect of exercise on postprandial lipaemia in children with sickle cell disease - Al Kitani, Mahfoodha (Frontiers in Sports and Active Living, 2025)
Elevated plasma triacylglycerol (TAG) levels are associated with endothelial dysfunction, inflammation, and increased vascular complications, particularly in populations such as individuals with sickle cell disease (SCD). This study aimed to investigate the effect of a single exercise session on postprandial TAG levels in children with SCD following the consumption of a high-fat meal. The high-fat meal was used to induce a significant postprandial increase in plasma triayglecrol (TAG) levels, aknown risk factor for endothelial dysfunction and vascular implication, particualry in population with Sickle Cell Disease (SCD). Twelve male children with SCD (mean age: 10.5 ± 1.2 years) participated in two 2-day trials, one involving brisk walking (exercise trial) and one with rest (rest trial), in a randomized, counter-balanced design. A mixed high-fat test meal (97 g fat, 124 g carbohydrate, 1,450 kcal) was administered after a 10-h overnight fast, and blood samples were collected at baseline, 60, 120, 240, 300, and 360 min post-meal to measure serum TAG, glucose, insulin, and total cholesterol concentrations. Postprandial TAG levels significantly increased in both trials, but the exercise trial showed a significantly lower TAG response compared to the rest trial (P < 0.05). The area under the curve (AUC) for TAG was greater in the rest trial than in the exercise trial (P < 0.05). Specifically, TAG concentrations were significantly lower in the exercise trial at 120 and 180 min post-meal (P < 0.05), indicating faster clearance of TAG following exercise. Insulin and glucose concentrations also increased post-meal, with significantly lower insulin and glucose AUC values in the exercise trial compared to the rest trial (P < 0.05). No significant differences were observed in total cholesterol between the two trials at 360 min post-meal. These findings suggest that a single bout of exercise prior to a high-fat meal reduces postprandial TAG concentrations in children with SCD, consistent with previous studies in healthy populations. The reduction in postprandial TAG may have implications for improving endothelial function and reducing the risk of cardiovascular and vaso-occlusive events in individuals with SCD. Further studies are needed to explore the long-term effects of regular exercise on lipid metabolism and disease complications in this population.